The Impact of English Club Activities on EFL Students’ Communicative Skills - Sheelan Ahmad Hamadameen; Qani Nasih Najim (Zanco Journal of Humanity Sciences)
This paper is concerned with the “Impact of English Club Activities on EFL Students’ Communicative Skills “. It aimed at finding out the extent to which English club has an effect on students’ competence and to modify students' attitudes towards the effect of English club activities. To achieve these aims, a set of questionnaire was designed for (63) students at the different stages at English Department, College of Basic Education-Salahaddin University in the academic year (2019-2020). After analyzing the results of the questionnaire, students' attitudes were greatly enhanced and have become more positive toward the effects of English club activities and they were interested in joining the English club very much.